Dynamics of care in families of patients with Systemic Arterial Hypertension in a community in Paraná (Research, Society and Development, 2022)
Objective: To understand, through a genogram, the dynamics of care in families with people with systemic arterial hypertension. Method: Qualitative, descriptive and exploratory research, with the participation of 3 families residing in a community in northwest Paraná. Data were collected through semi-structured interviews and analyzed by Bardin's Content Analysis. Results: Three categories emerged: Recognizing the new me: what do I feel? Losing the free self: who am I? e Preventing complications: what do I need to do? Recognition of symptoms is the first step in starting prevention and care methods. Knowing how to identify when blood pressure is altered can prevent future problems and facilitate treatment. Recognizing the need for a caregiver makes it possible to strengthen the strategies used by families to cope with the disease. Conclusion: The main difficulties encountered by the families were pointed out when facing the disease and preventive guidelines were produced on care with food, medication use, personal hygiene, and treatment methods.